Improving Conditions for Cooperative System Design: shifting from a product to a process focus - Grønbæk, Kaj; Grudin, Jonathan; Bødker, Susanne; Bannon, Liam J. (DAIMI Report Series, 1990)
This paper deals with the conditions for cooperation between users and developers in systems development projects. At first glance, many projects seem to present immense obstacles to user involvement. At the same time, there is a growing recognition of the need for user-developer cooperation, and research projects are providing new tools and techniques that engage users as full participants in system development. Two disparate projects serve as examples to frame a discussion of the realities of user involvement (or lack thereof) in development projects. This allows us to note both the possibilities for, and the obstacles to, user participation. We believe that cooperative systems design is needed to improve the quality of interactive computer applications, and that often it can be brought about even in the face of admitted obstacles. To achieve this, users need to be involved early in the whole process, and contracts governing development may need to be re-thought: inflexibility hinders iterative design, independent of the type of project under consideration. Development contracts should be shaped as process contracts between user and development organizations with scheduled renegotiation points. In general, we believe that the concern for quality products and processes requires that systems development assume more of a process focus than is currently evident.